Viðbrögð virknihópa plantna viðáburðargjöf ogútilokun beitar á íslenska hálendinu - Hanna Laufey Jónasdóttir 1992- (2021)
From the time of settlement the Icelandic highlands have undergone a drastic ecological change. This is partly due to climate and geological factors, but the introduction of large herbivores at the end of the 9th century had a strong influence on the ecosystems, especially those in the highlands. Nowadays, grazing practices in Iceland rely on extensive sheep grazing in summer rangelands, mainly located in the highlands, from June and until the autumn. Centuries of high grazing pressures in these ecosystems have driven some of them to a degraded state, with little chance of recovery unless active restoration measures are implemented. In this study, I use plant community data from a field experiment to examine the effects of two management practices, grazing exclusion and fertilization, on the cover of different plant functional groups after four years of treatment. Plant functional groups are groups of plants that share similar characteristics and functions in an ecosystem. In this study I categorized plants into three groups: facilitating, neutral and retarding, depending on their effects on ecosystem processes. Following my expectations, the facilitating group showed a positive response to the fertilizing experimental treatments and increased their cover in response to fertilization. The neutral plant functional group did not respond to the treatments, and the retarding group reduced its cover in favor of the facilitating group. Grazing exclusion did not show a strong effect on the cover of the different plant functional groups, but this was to be expected given the relatively short duration of the experiment (4 years). Grazing exclusion generally needs more time to have an effect on ecosystems than fertilization. Frá tímum landnáms hefur íslenska hálendið gengið í gegnum miklar vistfræðilegar breytingar. Þær hafa að hluta til orðið vegna breytinga á loftslagi og einnig vegna jarðfræðilegra þátta, en það má með sanni segja að innflutningur beitardýra til landsins í lok níundu aldar hafi haft gríðarleg áhrif á ...